Questions To Ask When Evaluating Tests - Rudner, Lawrence M.; ERIC Clearinghouse on Assessment and Evaluation (Washington, DC : ERIC Clearinghouse on Assessment and Evaluation, 1994)
The "Standards for Educational and Psychological Testing" of the American Educational Research Association, the American Psychological Association, and the National Council on Measurement in Education are intended to provide a comprehensive basis for evaluating tests. This digest identifies key standards applicable to most test evaluation situations. There must be a clear statement of recommended uses and a description of the population for which the test is intended. Samples used for validation and norming must be of adequate size and sufficiently representative to establish validity, appropriate norms, and test use for the stated purpose. The test must be reliable enough to permit stable estimates of individual ability, and it must predict academic performance adequately. Content and construct validity must be adequate, and the test must contain clear and detailed instructions for testing and reporting. The test must be neither biased nor offensive to any demographic group. Four additional readings are recommended. Sample questions to help in evaluation are presented for each of these areas. (SLD)
Availability: ERIC Clearinghouse on Assessment and Evaluation, The Catholic University of America, Department of Education, O'Boyle Hall, Washington, DC 20064 (free).
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RR93002002.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Ability; Academic Achievement; Evaluation Methods; Norms; Predictive Validity; Selection; Standards; Test Bias; Test Construction; Test Content; Test Reliability; Test Use; Test Validity; Tests; Standards for Educational and Psychological Tests; ERIC Digests; Guides, Non-Classroom.; ERIC Publications; ERIC Digests in Full Text